WEB RESOURCE ANALYSIS OF A PROFESSIONAL JOURNAL OF A SCIENTIFIC INSTITUTION BY MEANS OF MONITORING SYSTEMS - Spirin Олег; Ivanova Світлана; Kilchenko Алла; Novytska Тетяна (Journal of Information Technologies in Education (ITE), 2021)
The use of an open digital information-analytical system is a powerful auxiliary tool in conducting research and implementing their results. The article defines the services for open and commercial scientometric databases and webanalytics systems and describes the possibilities of their use for monitoring scientific professional publications, dissemination and use of the results of scientific and pedagogical research. The open scientometric services such as Google Scholar, information-analytical system "Bibliometrics of Ukrainian science", multifunctional universal service of web analytics Google Analytics, search system and database of scientific citations Open Ukrainian Citation Index, scientometric system Web of Science and scientometric, the Russian index of scientific citation for monitoring of the digital scientific professional journal "Information technologies and means of training" concerning the introduction of results of scientific and pedagogical researches are defined and described. In the course of the research the concept of monitoring of digital scientific professional publications was specified, ICT tools with approximate scientometric indicators for monitoring of digital scientific professional publications, dissemination and use of results of scientific and pedagogical researches were selected. The use of ICT tools for monitoring digital scientific professional publications allow tracking scientometric indicators, the relevance of the content of scientific publications, their ranking, the number of views, downloads and citations of digital versions of scientific products through the analysis of indicators. The main criteria for selecting scientometric databases and web analytics systems for monitoring professional publications are: openness, functionality and suitability for determining monitoring indicators. With the help of monitoring systems, you can evaluate the statistics of the publication, identify the main goals and adjust them to the desired parameters, fill the site according to the interest of visitors.